Blamestorming, Blamemongers and Scapegoats Allocating Blame in the Criminal Justice Process - Dingwall, Gavin (2008)
We live in a society that is increasingly preoccupied with allocating blame: when something goes wrong someone must be to blame. Bringing together philosophical, psychological, and sociological accounts of blame, this is the first detailed criminological account of the role of blame in which the authors present a novel study of the legal process of blame attribution, set in the context of criminalisation as a social and political process.